POTENSI USAHA DAN PENDIDIKAN KECAKAPAN HIDUP BERBASIS BUDAYA (MATA PENCAHARIAN) ‘SUKU ANAK DALAM’ - Kasiono Kasiono (Universitas Batanghari Jambi, 2018)
The life crises threatening Suku Anak Dalam (SAD)/ Orang Rimba are inevitable along with the difficulty of obtaining food and clean water sources in forests due to forest destruction and the widespread conversion of forests into plantations and industrial timber estates. Meanwhile, in the fulfillment of the necessities of life, SAD till now still has traditional livelihoods, namely: hunting and gathering, farming (cultivating), catching fish and selling honey and making handicrafts. This paper is a literature review with a view to knowing (1) Culture conected with the livelihood of Suku Anak Dalam (SAD); (2) Cultural-based Business Potentials in particular the livelihood of Orang Asli SAD; And (3) Life-based Life Skill Education needed by SAD. Based on this study, there are some potential SAD-based cultural enterprises / livelihoods, as follows: (a). Agricultural Enterprises, consisting of Wetland Farming and Dryland Farming; (B). Plantation Enterprises, consisting of Plantation of Hard Crops, Fruit Plantation, and Palawija Plantation; (C). The Livestock Business consists of 4-legged Animal Husbandry, Animal Husbandry of Poultry (Poultry Meat and Poultry Laying), Reptile Farm, and Beek Honey Farm; (D). Fishery Business, consist of Fishery Pond, Fishery of Karamba, and Ornamental Fish; (E). Handicraft Business, consisting of Wood and Rattan Handicraft, Leaf Handicraft, Grain-Based Handicraft, and Handicraft Traditional / Cultural Supplies; And (f). Business Trade Business Results. In connection with the potential Life Skills Education / Life Skill that can and should be given to SAD residents in facing the future is: (a). PKH of Agriculture Business Sector (a.1 Wetland Agriculture and a.2 Dryland Farming), (b). PKH Field of Plantation Business (b.1 Hard Crop Plantation, b.2 Fruit Plantation, b.3 Palawija Plantation), (c). PKH Livestock Business Field (c.1 Livestock Animal Farming 4, c.2 Animal Husbandry, (c.2.1 Poultry Broiler, c.2.2 Layer Poultry), c.3 Reptile Farm, c.4 Bee Honey Farm)); (D). PKH Fishery Business Sector, consists of d.1 Pond Fishery, d.2 Fishery of Karamba and d.3 Ornamental Fish; (E). PKH Field of Handicraft Business (e.1 Wood and Rattan Handicraft, e.2 Leaf Handicraft, e.3 Grain-Based Handicraft, e.4 Traditional / cultural Handicraft); And (f). PKH Field of Business Trade of Business Result.Keyword: Suku Anak Dalam (SAD), Business Potential, Life Skill Education, and Culture (Livelihood